Evaluasi Pelaksanaan Program Penyaluran Pupuk Bersubsidi bagi Petani di Kecamatan Sungai Tarab - Indah Defita; M. Fachri Adnan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This motivation of research was the issues of distributing subsidized fertilizers in Sungai Tarab District, namely the price of subsidized fertilizers is higher than the HET, subsidized fertilizers are not sufficient to meet the farmers needs and delays in the distribution of subsidized fertilizers. This research was conducted with the aim of conducting an implementation analysis and evaluation of the implementation of the subsidized fertilizer distribution program for farmers in Sungai Tarab District.The research method was descriptive qualitative and determining research informants using purposive sampling. The research location was conducted in Sungai Tarab District. The techniques for data collection were conducted through techniques by interview and documentation studies. Validity test of the data utilizing the source triangulation technique by cross-referencing data gathered from several sources. The collected data is then transcribed, re-read and then conclusions drawn. The results of the study show that the implementation of the subsidized fertilizer distribution program for farmers in Sungai Tarab Subdistrict has four factors which include communication, resources, attitude of implementers and bureaucratic structure.